2019
DOI: 10.1007/s00253-018-09611-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in high-level synthesis of the promising clinical drug, prodigiosin

Abstract: Prodigiosin, a red linear tripyrrole pigment and a member of the prodiginine family, is normally secreted by the human pathogen Serratia marcescens as a secondary metabolite. Studies on prodigiosin have received renewed attention as a result of reported immunosuppressive, antimicrobial and anticancer properties. High-level synthesis of prodigiosin and the bioengineering of strains to synthesise useful prodiginine derivatives have also been a subject of investigation. To exploit the potential use of prodigiosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 95 publications
1
59
0
Order By: Relevance
“…Thus, the results of the antioxidant activities reported in this study could support and enrich the available data on the antioxidant effects of PG. PG has been reported to be effective in inhibiting various cancerous cell lines without being toxic to normal cells; thus, it has been suggested as a potential molecular target in anticancer drugs [36]. To evaluate the inhibitory activity of the PG produced in this study, some cancerous cell lines, including A549, Hep G2, MCF-7, and WiDr, were investigated and tested.…”
Section: Antioxidant and Anticancers Activities Of Purified Pgmentioning
confidence: 99%
“…Thus, the results of the antioxidant activities reported in this study could support and enrich the available data on the antioxidant effects of PG. PG has been reported to be effective in inhibiting various cancerous cell lines without being toxic to normal cells; thus, it has been suggested as a potential molecular target in anticancer drugs [36]. To evaluate the inhibitory activity of the PG produced in this study, some cancerous cell lines, including A549, Hep G2, MCF-7, and WiDr, were investigated and tested.…”
Section: Antioxidant and Anticancers Activities Of Purified Pgmentioning
confidence: 99%
“…Prodigiosins are attracting more interest due to the antimicrobial activities ( Stankovic et al, 2014 ; Yip et al, 2019 ). It is reported that the cycloprodigiosin was more active against several kinds of bacteria than the linear form, prodigiosin ( Lee et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…As natural pigmented products, prodiginines have gained much more interests due to their antibacterial, antimalarial, algicidal, anticancer, immunosuppressive activities, and colorant for textile materials, etc. ( Soliev et al, 2011 ; Stankovic et al, 2014 ; Yip et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As for the construction of the pyrrole ring, it was achieved using the classic Paal-Knorr method from 40 (Scheme 10). Prodigiosin is a tripyrrole red pigment member of the prodiginine family; it is a secondary metabolite of the human pathogen Serratia marcescens [76]. This compound has been receiving growing attention owing to its reported antimicrobial, immunosuppressive, and anticancer properties.…”
Section: Pyrrol and Pyrazole And Derivativesmentioning
confidence: 99%
“…In 2014, El-Deiry and co-workers reported that prodigiosin is a promising p53 reactivator, restoring a deficient p53 signaling pathway and producing antitumor effects via a dual mechanism which involves p73 upregulation and disruption of the mutant p53/p73 complex. The first report on the total synthesis of prodigiosin dates back to 1962 [77], but other approaches have also been reported [76]. Tripathy, Lavallée and co-workers, for instance, reported the synthesis of fragment 42 via the reaction of 4-methoxy-3-pyrolin-2-one 41 with DMF in the presence of POBr 3 followed by the Suzuki cross-coupling between 42 and boronic acid 43 (Scheme 11) [78].…”
Section: Pyrrol and Pyrazole And Derivativesmentioning
confidence: 99%